Fourier Transform Infrared Spectroscopy of “Bisphenol A” - Ramzan Ullah; Ishaq Ahmad; Yuxiang Zheng (Journal of Spectroscopy)
FTIR (400–4000 cm−1) spectra of “Bisphenol A” are presented. Absorption peaks (400–4000 cm−1) are assigned on the basis of Density Functional Theory (DFT) with configuration as B3LYP 6-311G++ (3df 3pd). Calculated absorption peaks are in reasonable reconciliation with experimental absorption peaks after scaling with scale factor of 0.9679 except C-H and O-H stretching vibrations.